2021
DOI: 10.1186/s12905-021-01235-2
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up of inguinal endometriosis

Abstract: Background Inguinal endometriosis (IEM) is a rare extra pelvic endometriosis. Here, we study the clinical characteristics, management strategies, and long-term gynecological outcomes of IEM patients at Beijing Chaoyang Hospital. Case presentation Three patients presented with a total of four lesions (one on the left side, one on the right side, and one bilaterally). The diameters of the four lesions were 2 cm, 2 cm, 3.5 cm and 1.5 cm, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Observant management should be preferentially reserved for asymptomatic patients. Hormonal treatment has been underreported as a therapeutic strategy for inguinal endometriosis [14,15], and is typically reserved for patients who decline surgical management. In a small retrospective study, oral contraceptives were effective in symptomatic treatment of 1 of 4 patients without significant adverse effects, whereas dienogest effectively improved pain in 6 of 7 cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…Observant management should be preferentially reserved for asymptomatic patients. Hormonal treatment has been underreported as a therapeutic strategy for inguinal endometriosis [14,15], and is typically reserved for patients who decline surgical management. In a small retrospective study, oral contraceptives were effective in symptomatic treatment of 1 of 4 patients without significant adverse effects, whereas dienogest effectively improved pain in 6 of 7 cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…Catamenial symptoms (e.g., variations in mass size and tenderness) and magnetic resonance (MR) imaging findings can raise suspicion for inguinal endometriosis [4]. Frequently, patients undergo surgical procedures with a preoperative diagnosis of hernia, and endometriosis is incidentally discovered or identified through histologic examination [6,16]. Surgical excision may be the treatment of choice for inguinal endometriosis, but hormone medications can alleviate symptoms associated with endometriosis and serve as an alternation for patients who do not want surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the future estrogen/lncRNA-H19/miR-124-3p/ITGB3 pathway studies should be conducted in ecEECs and further in-vivo studies are also required. (3) The study had a relatively small sample size, especially in the control group, due to time and funding constraints. More studies with larger sample sizes are needed to confirm the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is one of the most prevalent gynecological disorders in women of reproductive age, 1,2 and is defined as the presence of endometrial-like tissue at sites other than the uterine cavity. [3][4][5][6] At present, the pathogenesis of endometriosis is still not understood well, 7 but ectopic endometrium will atrophy and the progress of endometriosis can be prevented by inhibiting ovarian function and decreasing estrogen level, suggesting that endometriosis is an estrogen-dependent disorder. At the same time, some previous studies showed that there was an increase estrogen level in endometriosis lesions, which explained the pathogenesis of postmenopausal endometriosis.…”
Section: Introductionmentioning
confidence: 99%